Tansong ginto alaala, lunan at ideolohiya sa loob at labas ng museo ng lilan = Fool's gold : memory, space and ideology inside and outside the museum of the few - Pangilinan, Carlo Gabriel S. (Plaridel, 2011)
This paper is a critical inquiry, assessment and re-reading of the permanent exhibit Gold of Ancestors : Pre-colonial Treasures in the Philippines at the Ayala Museum. The critiques employs the concepts of memory, space and ideology as vital theoretical positions and formulations, in order to criticize the exhibition, the museum and as such, to serve as a trope and discursive linkage in the critique of consumerism, capitalism and neo-liberal globalization as vital ideological imperatives that invisibly shape the field of other cultural and productions and spaces--such as the mall. It will try to look at the arena of the museum, as a concrete cultural, communicative and ideological space where traces and imprints of contending local and global discourses of history, power, class contradiction, capitalism and neo-liberalism are enmeshed.It's analysis would then serve as a grid in the interrogation of the mall as another distinct cultural sphere and facet of the capitalistic industry where similar issues of class, ideology, power relations and cultural imperialism are further heightened and actualized. In the end, this paper aims to contribute to the development of a counter-hegemonic and contrapuntal critique that would further strengthen the strategic position and politics of partisan scholarship in the academe.